1986
DOI: 10.1093/jac/18.6.693
|View full text |Cite
|
Sign up to set email alerts
|

In-vitro and in-vivo potency of five new fluoroquinolones against anaerobic bacteria

Abstract: The MICs of difloxacin (A-56619), A-56620 and ofloxacin were similar or within one to two-fold dilutions against a variety of anaerobic bacteria. Ciprofloxacin was slightly less active (two- to four-fold dilutions) than difloxacin, A-56620 and ofloxacin. Norfloxacin was less active than the other fluoroquinolones tested against anaerobic bacteria. The MICs of norfloxacin, A-56620, ciprofloxacin and ofloxacin against most anaerobes, except the Gram-positive cocci, were lower at pH 8.1 than at pH 6.6. MICs of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
19
0

Year Published

1988
1988
2013
2013

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(20 citation statements)
references
References 0 publications
1
19
0
Order By: Relevance
“…Only imipenem and metronidazole were active against all anaerobes. Overall, BAY y 3118 was more active than ciprofloxacin, sparfloxacin, piperacillin, cefotaxime, and clindamycin against the test isolates.Newer fluoroquinolone antimicrobial agents such as ciprofloxacin, ofloxacin, norfloxacin, lomefloxacin, and pefloxacin have been shown to have good activity against aerobic bacteria but usually have poor activity against most anaerobes, particularly the Bacteroides fragilis group (1,3,6,7,11 Our results confirm and extend the data regarding the in vitro activity of BAY y 3118 against anaerobes, particularly against those in the B. fragilis group. In the present study, we identified 5 of 435 (1%) anaerobes which were resistant (MICs of .4 ,ug/ml) to BAY y 3118; all were strains of the B. fragilis group.…”
supporting
confidence: 80%
“…Only imipenem and metronidazole were active against all anaerobes. Overall, BAY y 3118 was more active than ciprofloxacin, sparfloxacin, piperacillin, cefotaxime, and clindamycin against the test isolates.Newer fluoroquinolone antimicrobial agents such as ciprofloxacin, ofloxacin, norfloxacin, lomefloxacin, and pefloxacin have been shown to have good activity against aerobic bacteria but usually have poor activity against most anaerobes, particularly the Bacteroides fragilis group (1,3,6,7,11 Our results confirm and extend the data regarding the in vitro activity of BAY y 3118 against anaerobes, particularly against those in the B. fragilis group. In the present study, we identified 5 of 435 (1%) anaerobes which were resistant (MICs of .4 ,ug/ml) to BAY y 3118; all were strains of the B. fragilis group.…”
supporting
confidence: 80%
“…It also has excellent pharmacokinetic properties (27). The N-1-fluoro-substituted phenyl substitution may improve the in vitro efficacy of quinolones against anaerobic bacteria, as exemplified by tosufloxacin (17), difloxacin (18), and temafloxacin (28).…”
Section: Structure-activity Relationshipsmentioning
confidence: 99%
“…Activity against the Bacteroides fragilis group organisms has been poor, in general (2,4,5,8,9,15,18). Variable activity against Prevotella species, such as the Prevotella melaninogenica and Prevotella oralis group, and against Bacteroides ureolyticus has been reported (8).…”
mentioning
confidence: 99%